PD-1/PD-L1 blockade enhances the efficacy of SA-GM-CSF surface-modified tumor vaccine in prostate cancer. (10th October 2017) - Shi, Xiaojun; Zhang, Xinji; Li, Jinlong; Zhao, Hongfan; Mo, Lijun; Shi, Xianghua; Hu, Zhiming; Gao, Jimin; Tan, Wanlong
Abstract: Program death receptor-1 (PD-1)/program death ligand 1 (PD-L1) signaling plays an important role in tumor adaptive immune resistance. The streptavidin-granulocyte-macrophage colony stimulating factor (SA-GM-CSF) surface-modified tumor cells vaccine developed through our novel protein-anchor technology could significantly promote the activation of dendritic cells. Although GM-CSF vaccine could significantly increase the number of tumor-specific CD8 + T-cells, the majority of these CD8 + T-cells expressed PD-1. Moreover, GM-CSF vaccine up-regulated the PD-L1 expression of tumor cells, resulting in immune resistance. Adding PD-1/PD-L1 blockade to GM-CSF vaccine therapy could significantly increase the population of CD4 + T, CD8 + T and CD8 + IFN-γ + T but not CD4 + Foxp3 + T-cells and induced the highest production of IFN-γ. PD-1/PD-L1 blockade could effectively rescue the tumor-specific T lymphocytes generated by the GM-CSF vaccine, resulting in consistent tumor rejection. Taken together, PD-1/PD-L1 blockade combined with SA-GM-CSF-modified vaccine could effectively induce a strong specific antitumor immune response against prostate cancer. Highlights: PD-L1/PD-1 signaling negatively affects the immune response in tumor microenvironment. GM-CSF vaccine could up-regulated the PD-L1 expression in tumor microenvironment. Anti-PD-1 enhances the efficacy of GM-CSF vaccine in the treatment of prostate cancer.